Enrichment of intestinal Lactobacillus by enhanced secretory IgA coating alters glucose homeostasis in P2rx7−/− mice - Perruzza, Lisa; Strati, Francesco; Gargari, Giorgio; D’Erchia, Anna Maria; Fosso, Bruno; Pesole, Graziano; Guglielmetti, Simone; Grassi, Fabio (Scientific reports, 2019)
The secretory immunoglobulin A (SIgA) in mammalian gut protects the organism from infections and contributes to host physiology by shaping microbiota composition. The mechanisms regulating the adaptive SIgA response towards gut microbes are poorly defined. Deletion of P2rx7 , encoding for the ATP-gated ionotropic P2X7 receptor, leads to T follicular helper (Tfh) cells expansion in the Peyer’s patches (PPs) of the small intestine, enhanced germinal centre (GC) reaction and IgA secretion; the resulting alterations of the gut microbiota in turn affects host metabolism. Here, we define gut microbiota modifications that correlate with deregulated SIgA secretion and metabolic alterations in P2rx7 −/− mice. In particular, Lactobacillus shows enhanced SIgA coating in P2rx7 −/− with respect to wild-type (WT) mice. The abundance of SIgA-coated lactobacilli positively correlates with Tfh cells number and body weight, suggesting Lactobacillus -specific SIgA response conditions host metabolism. Accordingly, oral administration of intestinal Lactobacillus isolates from P2rx7 −/− mice to WT animals results in altered glucose homeostasis and fat deposition. Thus, enhanced SIgA production by P2X7 insufficiency promotes Lactobacillus colonization that interferes with systemic metabolic homeostasis. These data indicate that P2X7 receptor-mediated regulation of commensals coating by SIgA is important in tuning the selection of bacterial taxa, which condition host metabolism.